2021
DOI: 10.2196/24515
|View full text |Cite
|
Sign up to set email alerts
|

Unique Features of a Web-Based Nutrition Website for Childhood Cancer Populations: Descriptive Study

Abstract: Background Children with cancer experience a myriad of nutritional challenges that impact their nutrition status during treatment and into survivorship. Growing evidence suggests that weight at diagnosis impacts cancer outcomes, but provider guidance on nutrition and diet during treatment varies. Nutrition literacy and culinary resources may help mitigate some common nutritional problems; however, many patients may face barriers to accessing in-person classes. Along with dietitian-led clinical inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Overall, the participants reported positive feedback for low‐sucrose and low‐fat meal options and patients preliminarily indicated willingness to maintain a diet intervention during treatment composed of recipes that were low sucrose or low fat (Figure 2D). All recipes are freely available on a website created by our group, 12 and both participants and their parents were provided print materials directing them to the e‐cookbook site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the participants reported positive feedback for low‐sucrose and low‐fat meal options and patients preliminarily indicated willingness to maintain a diet intervention during treatment composed of recipes that were low sucrose or low fat (Figure 2D). All recipes are freely available on a website created by our group, 12 and both participants and their parents were provided print materials directing them to the e‐cookbook site.…”
Section: Resultsmentioning
confidence: 99%
“…After obtaining informed consent and assent, 12 (nine of which were diagnosed with standard risk B-ALL) study participants were recruited in Houston, Texas from the MD Anderson Cancer Center Children's Cancer Hospital in accordance with approval from the Institutional Review Board of the University of Texas MD Anderson Cancer Center (2010-0654). Eligibility criteria included children being school aged (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), pediatric cancer patients who were currently undergoing treatment, and ability to read and speak English. Each participant attended in-person sessions wherein they tasted five low-fat prepared foods and five low-sucrose prepared foods prepared by the Bionutrition Research Core at MD Anderson Cancer Center using recipes from the At The Table online cookbook.…”
Section: Observational Study Of Diet Receptivitymentioning
confidence: 99%
“…Currently, several approaches are being implemented targeting the family-based nutrition and cooking education of parents and guardians of children with cancer [ 71 , 72 , 73 ]. Among such interventions, web-based dietary and cooking intervention approaches have gained great attention among parents and young patients [ 74 , 75 , 76 ]. Preliminary results have shown that early interventions resulted in better nutrition practices, i.e., lower sodium consumption [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their development process, user statistics for the year after their launch (ie, May 2014-May 2015), including total page views, total visitors, and region of user’s residence, were reported; however, details such as demographic, health behavior, and clinical characteristics about their users were not described [ 12 ]. A similar project of developing a web-based cookbook for pediatric patients with cancer, undertaken by the MD Anderson Cancer Center in Texas, has also been described [ 25 ] and compared to two other science-based cancer and nutrition websites, including Cook for Your Life [ 26 ]; however, information about the characteristics of their users was not provided.…”
Section: Discussionmentioning
confidence: 99%